Comparative Evaluation of Chlorhexidine, Herbal Mouthwash (Amarantha), and Probiotic Mouthwash (Oralvit) on Plaque Index: An Observational Study (Academia Journal of Medicine, 2025)
Background: Dental plaque is the primary etiological factor for gingivitis and periodontal diseases. Mouthwashes are widely used as adjuncts to mechanical plaque control. Chlorhexidine (CHX) is the gold standard, whereas herbal and probiotic formulations are gaining popularity due to their safety and patient acceptance. Aim: To compare the Plaque Index (PI) reduction produced by 0.12% chlorhexidine, a herbal mouthwash (Amarantha), and a probiotic mouthwash (Oralvit Probiotic Anti-Plaque) in an in vivo population. Materials and Methods: An in vivo comparative study was conducted on 45 participants aged 18–40 years with mild to moderate plaque accumulation. Subjects were randomly divided into three groups: Group A (0.12% CHX), Group B (Amarantha herbal mouthwash), and Group C (Oralvit probiotic mouthwash). Plaque Index (Silness & Löe, 1964) was recorded at baseline, day 7, day 14, and day 28. Results: All groups showed significant reductions in plaque scores over time. CHX demonstrated the most rapid reduction at day 7, while the herbal and probiotic groups showed progressive reductions, with comparable efficacy to CHX by day 28. Conclusion: Chlorhexidine remains the most effective short-term antiplaque agent. Herbal and probiotic mouthwashes show comparable plaque reduction over longer durations and may serve as effective alternatives for long-term use.
Keywords: Chlorhexidine; Plaque; Probiotic Mouthwash